2022
DOI: 10.3390/ph15080968
|View full text |Cite
|
Sign up to set email alerts
|

Ag2O Nanoparticles as a Candidate for Antimicrobial Compounds of the New Generation

Abstract: Antibiotic resistance in microorganisms is an important problem of modern medicine which can be solved by searching for antimicrobial preparations of the new generation. Nanoparticles (NPs) of metals and their oxides are the most promising candidates for the role of such preparations. In the last few years, the number of studies devoted to the antimicrobial properties of silver oxide NPs have been actively growing. Although the total number of such studies is still not very high, it is quickly increasing. Adva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 150 publications
1
30
0
Order By: Relevance
“…Silver oxide NPs, a type of silver nanoparticle, have been the subject of extensive research due to the antibacterial effects they are thought to have. Silver oxide NPs have little cytotoxicity to eukaryotic cells, show significant antibacterial and antifungal properties, and are relatively simple to produce [ 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…Silver oxide NPs, a type of silver nanoparticle, have been the subject of extensive research due to the antibacterial effects they are thought to have. Silver oxide NPs have little cytotoxicity to eukaryotic cells, show significant antibacterial and antifungal properties, and are relatively simple to produce [ 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…OXD usually participates in redox reactions at the expense of the molecular oxygen (O 2 ), which is reduced to H 2 O 2 or H 2 O. Comotti et al reported that small-sized gold nanoparticles (AuNPs) could promote the glucose to converse into the gluconate, which behaves similarly, to glucose oxidase (GOx) ( 50 ). Since then, ultra-small nanomaterials based on noble metals, such as Au ( 51 , 52 ), Ag ( 53 ), Pt ( 54 ), and Ir ( 55 ) have been demonstrated to be capable of OXD simulation. Gold nanoparticles (AuNPs) are effective nanomaterial-based enzyme mimics (nanozymes) for enzymatic reactions under mild conditions.…”
Section: Noble Metal Biomimetic Nanozymesmentioning
confidence: 99%
“…Consequently, AgNPs have become a promising nanomaterial for various specific applications [ 17 ]. That pathogenic microorganisms are not resistant to certain nanomaterials makes AgNPs a potential pesticide [ 18 , 19 ]. There are studies that indicate that the intrinsic toxicity of AgNPs depends mainly on factors such as size, shape, surface area, surface charge, solubility, the state of agglomeration of these, and the presence of other compounds [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, sustainable nanoparticle synthesis methodologies have been investigated in order to avoid or reduce the polluting problems that are commonly generated by different products for agricultural use such as pesticides and herbicides [ 23 , 24 ]. The green synthesis of AgNPs has been an excellent alternative, since this methodology is friendly to the environment by using ecological solvents such as water and ethanol, among others [ 19 , 24 , 25 ] and where the main factors that determine the size, concentration, and stability of the nanoparticles are the temperature and the concentration of silver salt, in addition to the plant extract that acts as a reducing agent in the reaction kinetics during the nanoparticle synthesis process [ 25 , 26 ]. In this research work, we used the extract of the leaves of the Geranium plant as a reducing agent.…”
Section: Introductionmentioning
confidence: 99%